"Introduction to Vertical Hydroponics for the Community of Ardirejo Village to Achieve Food Security: Pengenalan Hidroponik Vertikultur Pada Masyarakat Kelurahan Ardirejo Sebagai Upaya Kemandirian Pangan - Purnamasari, Ika; Yagus Wijayanto; Suci Ristiyana; Tri Wahyu Saputra; Zaky Firmansyah Maulana; Yeremia Rivieri; Ersya Kamelia Rosana; Kharisma Adi Bagaskara (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Ardirejo Village, Panji Subdistrict, is one of the villages located in the center of Situbondo Regency. Limited agricultural land is the main challenge in meeting the food needs of the local community. An innovative approach to maximizing land use is required, one of which is through vertical farming technology. A community service program was conducted in Ardirejo Village to support the community’s food security. By involving active participation from the local community, this program not only provides practical solutions but also aims to empower the community to produce food independently. First, a comprehensive survey was conducted to identify the main issues and the characteristics of the land in Ardirejo Village. The results of the situational analysis were used to select plants suitable for the land conditions and to design an efficient vertical farming structure. Afterward, workshops were held for the local women’s organization (PKK) and the community on the concept of vertical farming, appropriate plant selection, and necessary care techniques. Regular monitoring and mentoring were provided to the community to ensure the smooth implementation of vertical farming practices. This program also incorporates ongoing education and extension approaches to ensure the community’s knowledge continues to grow. With a better understanding of vertical farming and sustainable agricultural practices, the community is expected to actively manage and utilize this technology."